The Effect of Vitamin D Level on the Clinical Course of the Disease in Patients with Lower Respiratory Tract Infection - Demet Kangel; Asuman Kıral (Cam & Sakura Medical Journal)
Objective: Vitamin D deficiency is a significant public healthcare issue worldwide. New research suggests that there is a link between vitamin D deficiency and the progression of various infectious diseases, particularly viral infections. The aim of this study is to evaluate the impact of vitamin D deficiency on the clinical course of lower respiratory tract infections (LRTIs) in hospitalised infants. Material and Methods: This retrospective study included 178 pediatric patients (113 males, 65 females) aged 1-24 months, hospitalized with LRTI between October 15, 2017, and May 15, 2019. Patients were categorized into vitamin D deficient (<12 ng/mL, n=22), insufficient (12-20 ng/mL, n=31), and sufficient (>20 ng/mL, n=125) groups. Demographic, socio-economic, nutritional, and clinical characteristics were compared. The severity of LRTI was assessed using the Modified Wang Respiratory Scoring System. The association between indicators of disease severity [Wang score, intensive care unit (ICU) admission, oxygen therapy, length of hospitalization, and respiratory support] and vitamin D levels was analyzed. Results: The mean 25(OH)D level was 26.53±12.14 ng/mL. A total of 29.78% (n=53) of patients had vitamin D levels below 20 ng/mL. Vitamin D levels were significantly higher in infants who received regular vitamin D supplementation during the first six months and in those who were fed with formula (p<0.001). Patients with severe LRTI had noticeably lower vitamin D levels than those with mild-to-moderate cases (median: 21.20 ng/mL vs. 27.20 ng/mL, p=0.021). Vitamin D deficiency was found to be an independent risk factor for severe LRTI [odds ratio (OR): 4.32, 95% confidence interval (CI): 1.63-11.47], ICU admission (OR: 4.74, 95% CI: 1.73-12.94), and the need for oxygen support (OR: 2.74, 95% CI: 1.30-5.96). Conclusion: Vitamin D deficiency appears associated with more severe clinical courses in infants with LRTI. Optimizing vitamin D status could reduce morbidity. Larger prospective studies are warranted.